The Influence Of Leadership And Work Environment On Employee Performance At The Office Of The Secretariat Of The Lahat Regency Legislature - Nidyawati Nidyawati; Melia Handayani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of leadership and work environment on employee performance at the Lahat Regency DPRD Secretariat Office. The sample in this study amounted to 42 respondents who were distributed to employees at the Lahat Regency DPRD Secretariat Office. The data analysis method used is quantitative analysis using Data Quality Test (Validity Test and Reliability Test), Inferential Statistical Test (Multiple Linear Regression, Correlation Coefficient, Coefficient of Determination, t test, and F test). The results of the analysis obtained Leadership has a positive and significant effect on Employee Performance at the Lahat Regency DPRD Secretariat Office, this can be seen from the t value (4.214) > t table (2.023). And the Work Environment has a positive and significant effect on Employee Performance at the Lahat Regency DPRD Secretariat Office, this can be seen from the t value (3,207) > t-table (2,023). And Leadership and Work Environment have a positive and significant effect on Employee Performance at the Lahat Regency DPRD Secretariat Office, this can be seen from the calculated F value (25.463) > F table (4.091) and the significance value < the significance level (α) 0.05 (0.000 < 0.05).